EVALUASI PERILAKU OPERATOR PENGGERGAJIAN DENGAN PENDEKATAN METODE BEHAVIOR BASED SAFETY (BBS) - CAHYONO, DIMAS EKO (JUSTI (Jurnal Sistem dan Teknik Industri), 2024)
Perum Perhutani KBM IK (Wood Industry Independent Business Unit) Gresik is an organizational unit under the East Java Unit II Perum Perhutani office which is responsible for the implementation of business management in the wood industry. The company's activity (wood industry) is processing log raw materials from the production of Perum Perhutani itself or producing logs from other areas with the aim of obtaining added value. In producing these products, Perum Perhutani KBM IK Gresik in the production process uses a variety of machining tools and requires concentration. However, the existence of these machines in the production process cannot be separated from the name of a work accident. Therefore it is necessary to take an approach to reduce the risk of work accidents. This study uses the Behavior Based Savety (BBS) method approach with the DOIT (Define, Observ, Intervene, Test) model which aims to change from unsafe behavior to safe behavior. Unsafe Behavior leads to work accidents such as working without paying attention to safety, doing work without license, operating at breakneck speeds, using non-standard equipment. Based on the research results identified the stages of work that resulted in work accidents that occur due to unsafe behavior. That is, when placing logs on the rolling track, the operator does not use safety shoes, when workers pick up pieces of the board by the bandsaw machine, the operator does not use safety gloves, the operator takes wood from the pile with an incorrect take position and when cleaning the saw blade from dust the operator does not pay attention to the dangers that threaten.